Behavioral Science & Policy: Volume 1, Issue 2 (Book collections on Project MUSE., 2016)
The success of nearly all public- and private- sector policies hinges on the behavior of individuals, groups, and organizations. Today, such behaviors are better understood than ever, thanks to a growing body of practical behavioral science research. However, policymakers often are unaware of behavioral science findings that may help them craft and execute more effective and efficient policies. The pages of this new journal will become a meeting ground: a place where scientists and non-scientists can encounter clearly described behavioral research that can be put into action. By design, the scope of BSP is broad, with topics spanning health care, financial decisionmaking, energy and the environment, education and culture, justice and ethics, and work place practices. Contributions will be made by researchers with expertise in psychology, sociology, law, behavioral economics, organization science, decision science, and marketing. The journal is a key offering of the Behavioral Science & Policy Association in partnership with the Brookings Institution. The mission of BSPA is to foster dialog between social scientists, policymakers, and other practitioners in order to promote the application of rigorous empirical behavioral science in ways that serve the public interest. BSPA does not advance a particular agenda or political perspective. The first issue's contents follow. Behavioral Science & Policy, vol. 1, no. 2 Extending the reach of behavioral policy Editors' note: Craig R. Fox & Sim B. Sitkin 1. Belonging nowhere: Marginalization and radicalization risk among Muslim immigrants, Sarah Lyons-Padilla, Michele J. Gelfand, Hedieh Mirahmadi, Mehreen Farooq, & Marieke van Egmond 2. New directions for policies aimed at strengthening low-income couples, Justin A. Lavner, Benjamin R. Karney, & Thomas N. Bradbury 3. A personal touch in text messaging can improve loan repayment, Dean Karlan, Melanie Morten, & Jonathan Zinman 4. Beyond good intentions: Prompting people to make plans improves follow-through on important tasks, Todd Rogers, Katherine L. Milkman, Leslie K. John, & Michael I. Norton 5. Improving the communication of uncertainty in climate science and intelligence analysis, Emily H. Ho, David V. Budescu, Mandeep K. Dhami, & David R. Mandel 6. Moving citizens online: Using salience and message framing to motivate behavior change, Noah Castelo, Elizabeth Hardy, Julian House, Nina Mazar, Claire Tsai, & Min Zhao 7. Blinding prosecutors to defendants' race: A policy proposal to reduce unconscious bias in the criminal justice system, Sunita Sah, Christopher T. Robertson, & Shima B. Baughman 8. The White House social and behavioral sciences team: Lessons Learned from Year One, William J. Congdon & Maya Shankar.